PENGARUH CORPORATE SOCIAL RESPONSIBILITY, CAPITAL INTENSITY, DAN CORPORATE RISK TERHADAP TAX AVOIDANCE - Cintia Aulia Ramadanti (2021)
This research aims to determine the effect of corporate social responsibility, capital intensity, and corporate risk on tax avoidance in property and real estate sector companies listed on Indonesia Stock Exchange for the period 2016-2019. This is a quantitative with secondary data research that consisted of 101 samples that collected using purposive sampling method. The hypothesis test used in this study is multiple linear regression using IBM SPSS 26 software. The result of this study indicates that (1) corporate social responsibility has no effect on tax avoidance, (2) capital intensity has a significant negative effect on tax avoidance, and corporate risk has a significant positive effect on tax avoidance. The implication of this study is to contribute new findings in the research area in the field of taxation, especially in tax avoidance, corporate social responsibility, capital intensity, and corporate risk.